Diversity of Pollinator Insects in Relation to Seed Set of Mustard (Brassica rapa L.: Cruciferae) - TRI ATMOWIDI; DAMAYANTI BUCHORI; SJAFRIDA MANUWOTO; BAMBANG SURYOBROTO; PURNAMA HIDAYAT (Bogor Agricultural University, Indonesia, 2007)
Pollinators provide key services to both natural and agricultural ecosystems. Agricultural productivity depends, in part, on pollinator populations from adjacent seminatural habitats. Here we analysed the diversity of pollinator insects and its effect to seed set of mustard (Brassica rapa) planted in agricultural ecosystem near the Gunung Halimun-Salak National Park, West Java. At least 19 species of insects pollinated the mustard, and three species, i.e. Apis cerana, Ceratina sp., and Apis dorsata showed a high abundance. The higher abundance and species richness of pollinators occurred at 08.30-10.30 am and the diversity was related to the number of flowering plants. Insect pollinations increased the number of pods, seeds per pod, seed weights per plant, and seed germination. Key words: diversity, pollinator insects, social bees, solitary bees, seed set, Brassica rapa